The effect of time of day and high intensity exercise on cognitive performances of elite adolescent karate athletes - Khemila, S.; Romdhani, M.; Abedelmalek, S.; Chtourou, H.; Souissi, M. A.; BenTouati, E.; Souissi, N. (Chronobiology International, 2022)
To explore the effect of time of day (TOD) on several components of cognitive performance prior and post to a physically exhaustive task in a sample of adolescent elite athletes. In a counterbalanced and randomized order, fourteen highly trained male karate athletes (17 ± 0.96 years; 1.75 ± 0.07 m; 68.0 ± 9.50 kg; BMI 22.15 ± 0.54 kg.m-2) completed two test sessions at 09h00 and 16h00. Cognitive performance was evaluated before and after the karate specific test (KST). During each session, participants completed the profile of mood state (POMS), simple (SRT) and choice (CRT) reaction times, comparison test (COMT), mental rotation test (MRT), egocentric distance estimation (DE), and the rating of perceived exertion (RPE). KST was not TOD dependent (p > .05, d = 0.33). RPE scores were higher in the afternoon compared to the morning (p < .05, d = 0.68). Before the KST, SRT (p < .01, d = 0.69), CRT (p < .01, d = 0.47), COMT (p < .01, d = 0.62) and MRT (p < .001, d = 0.65) were better in the afternoon than in the morning. However, DE was not affected by the TOD (P > .05). KST improved SRT (p < .01, d = 0.078), CRT (p < .001, d = 0.72), COMT (p < .001, d = 1.31) and MRT (p < .001, d = 0.80) performances only in the morning. Cognitive performances are TOD dependent with higher performances realized in the afternoon. Performing a high intensity exercise in the morning, but not in the afternoon, enhanced several aspects of cognitive performances. The current results indicate that an intensive warm-up could be beneficial when a morning competition requires high cognitive readiness.